UTILIZING VLOG IN YOUTUBE TO INCREASE STUDENTS’ INTERESTING IN SPEAKING ENGLISH LEARNING AT THE FIRST SEMESTER STUDENTS’ OF ENGLISH LANGUAGE EDUCATION UNIVERSITAS ISLAM SYEKH YUSUF IN ACADEMIC YEAR 2019/2020 - Isnaniah Isnaniah (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2020)
The research focused on increasing students’ interesting in speaking English learning by using video as media. This study aims to find out how YouTube contributes the developments of students’ speaking English skill. It is an action research on the first semester students of English language education in the academic year 2019/2020. As we know that speaking is one of the most important skills in language to be learnt in English as a foreign language. Unfortunately, When the writer observed before doing the research the writer found that the students still have the problems in learning speaking English. It was because they are not interest or confidence when they have to speak in front their friend. Therefore, to solve the problems, the writer tried to use utilizing vlog in YouTube as media in learning speaking English. Utilizing vlog in YouTube could increase the students’ interesting in speaking English learning.  It was proved by the result of output test statistic in Mann-Whitney that showed the result score Asymp. Sig (2-tailed) 0.000 was smaller than probability score 0.05. It was calculated by SPSS version 24. In other words, using YouTube as media has given contribution to improve students’ speaking English skill